The Proper Law as a Choice of Law in Contract Design - Muhammad Azkannasabi; Hardian Iskandar (Jurnal Justiciabelen, 2024)
International Contract Law is a bridge that connects agreements made by the world community. However, cooperation that occurs often encounters obstacles when the disputing parties do not fulfill their achievements. So that the aggrieved party usually resolves disputes through the courts. However, the settlement of international civil contract disputes through the courts often causes dissatisfaction for the defeated party because the judge in the court must determine the lex cause (law that should apply) first. However, sometimes the judge or the party in trouble does not know much about the lex cause in general, not to mention the existence of non-juridical factors that greatly influence the judicial process so that these conditions usually result in unsatisfactory decisions. So that the solution to overcome this matter, the parties can make a choice of law (the choice of law or the choice of forum) so that it is expected to obtain a satisfactory decision in the settlement of disputes arising in International Civil Contracts for the parties to the dispute. The Proper Law in a contract is the legal system desired by the parties, or if the will is not expressly stated or cannot be known from the surrounding circumstances, then the choice of law seen from the most reasonable state law applies to the contract, namely by look for the center of gravity or the link point that is closest to the contract. The Proper Law theory builds on flexibility rather than offering mechanical rules so it provides more certainty than other closest relationship tests. The research method used is normative juridical research, namely legal research conducted by examining secondary data with an emphasis on library research. So that the results of the research and discussion find solutions to problems that use the principles of The Proper Law as a solution to solving problems. namely legal research conducted by examining secondary data with an emphasis on literature studies. So that the results of the research and discussion find solutions to problems that use the principles of The Proper Law as a solution to solving problems. namely legal research conducted by examining secondary data with an emphasis on literature studies. So that the results of the research and discussion find solutions to problems that use the principles of The Proper Law as a solution to solving problems.